Efektivitas CBIA-Narkoba dalam Peningkatan Pengetahuan Remaja untuk Menolak Narkoba - Sinta Rachmawati; Sri Suryawati; Rustamaji Rustamaji (Media Kesehatan Masyarakat Indonesia, 2018)
Drug abuse is still a major health problem in Indonesia. The lecture method is one of the most widely usedto provide information, including drug. CBIA (Community Based Interactive Approach) drug is an alternativeeducational method that involves small group discussion. This study aims to assess the effectiveness of CBIA-Drugcompared with lecture method in improving youth knowledge to resist drug. Quasi experimental with pre test-posttest control group design was used in this study. It involved 30 respondents for CBIA-Drug group, 30 respondentsfor intervention group and 30 respondents for control group. Mutivariate statistical analysis (kruskall wallis)was used to evaluate the effectiveness of CBIA-Drug. There was a significance value at post test 1 for each group(p<0.05). It means that CBIA-Drug is more effective in improving youth knowledge to resist drug than lecturemethod.